Jelis Knijff en Jelis Jelissen, kistenmaker in Zwolle en beeldsnijder in Kampen (Bulletin KNOB, 2001)
A problem is that the limited accessibility of the rich archives in Zwolle and Kampen as yet stands in the way of a reconstruction of the families of Jelis Knijff and Jelis Jelissen. It cannot even be excluded that it concerns a father and son here. Cabinetmaker Jelis Knijff became a citizen of Zwolle in 1531 and, just as Colijn de Nole, got involved in a fight with mr. Vrerick in 1543.This mr. Vrerick worked at the benches for the new council chamber in Kampen, while Colijn de Nole was making the famous fireplace in his Utrecht workshop. Mr. Vrerick experienced the presence of competitor Jelis Knijff from Zwolle as a threat, which resulted in a row in the Wine Cellar of Kampen.Besides Jelis Knijff, other cabinetmakers known to have lived in Zwolle in approximately the same period are Albert and Berent Knijff. Furthermore, around 1550 the names of Willem, Anna and Berthe Knijff are mentioned in the Zwolle card system. In a cartulary we read that Jelis Knijff owned a house in the Koestraat in Zwolle at the side of the town wall and in another source that he was still alive in 1579.The only thing we know about Jelis Jelissen is that he was guild master and hence a citizen of Kampen and that his death was memorised there in 1573. Mr. Jelis Jelissen supplied the stone pillars of a rack for the town hall in Zwolle and he is also said to have designed the never executed fireplace for the council chamber of the town hall in Zwolle. A vague signature of a double capital J appears to confirm this new attribution.Just as Colijn de Nole, Arnt van Tricht and later Claesz Jellesz., Jelis Jelissen had a thorough command of both carving sculptures in wood and hewing stone. Jelis is said to have been a wilful artist who was also a skilled draughtsman. A comparable versatility brought Colijn de Nole in conflict with the Utrecht guild of bricklayers and masons in 1532, but he refused to take on this guild as well. However, in 1557 Jelis Jelissen bowed for the threat of fines, became a member and rose to be guild master in both organisations.